EKONOMI SYARIAH DALAM ETIKA PEMERATAAN RESIKO - Masyhuri (Jurnal Ekonomi dan Pembangunan, 2025)
This article aims at addressing how importance is the role of musyarakah and revenue sharing systems in the Indonesian small scale fishing industry. From syari’ah perspective and qualitative analysis, it is orgued that the systems play an important role in the development of fishing sector. The sea fishing industry is a capital-intensive and also a high risky industry,while investment for fisherman is still a crucial problem. Musyarakah provides the syar’i manner of how fishermen obtain their financial needs, while revenue sharing constitutes the manner of how fishermen manage their uncertainly income. Both of them become institutionalized as a result of the adaptation of fisherman to the capital-intensive and a high risky of sea fishing industry. Such institutions should be important as a basic in lounching of the policy development of fishing sector.